Effectiveness and mechanism of nano iron oxides modified halloysite nanotubes for uranium sequestration. Issue 2 (April 2023) - Su, Minhua; Ou, Tao; Li, Jiayi; Tong, Lizhi; Han, Weixing; Wu, Yuhua; Chen, Diyun
Abstract: Uranium mining and nuclear energy production have resulted in large amounts of uranium (U) -containing radioactive wastewater. Many silicate minerals such as halloysite nanotubes (HNTs) enriched in Fe, Al and Si can exhibit unique properties of high plasticity, thermal stability, and high nuclide blocking ability and be used to treat uranium-containing wastewater. Herein, nanorod composites of HNTs loaded with α-Fe2 O3 (He-HNTs) and Fe3 O4 (Ma-HNTs) were innovatively used to sequestrate uranyl ions via adsorption process. The adsorption equilibrium could be achieved within a relatively short contact time (i.e ., 40 min). The maximum adsorption capacities of U(Ⅵ) ions by He-HNTs and Ma-HNTs were 74.64 and 66.40 mg/g, respectively. Ma-HNTs exhibited excellent magnetic separation performance when used to treat uranium-containing radioactive wastewater. Humic acid generally inhibited the sequestration of U(Ⅵ) by either He-HNTs or Ma-HNTs under high pH conditions. SO4 2− and high valent cations impeded the interaction that occurred among U(Ⅵ) and Ma-HNTs under high pH conditions. Ion exchange, surface complexation and electrostatic interactions dominated the sequestration behavior of U(Ⅵ) on He-HNTs as well as Ma-HNTs. In addition, reduction was involved in the Ma-HNTs- U(Ⅵ) system, leading to greater U(VI) removal efficiencies. The iron oxide- halloysite composites are very promising to be used for the treatment of uranium(VI)-containing wastewater. Graphical Abstract: ga1 Highlights: Either α-Fe2 O3 or Fe3 O4 was loaded on halloysite nanotubes successfully. Both α-Fe2 O3 -halloysite and Fe3 O4 -halloysite displayed outstanding U(VI) sequestration performance. Humic acid suppressed U(VI) sequestration under high pH conditions. Surface complexation and electrostatic interactions dominated the U(Ⅵ) sequestration. Reduction was involved in the system in the presence of Ma-HNTs.